Nurses - Workforce Commodity, or Autonomous Professionals: What Nurses Know about their Value, Working Conditions, Impacts on Patient Care, and Nursing Practice Concerns - Anna Power-Horlick (York University Libraries, 2023)
The current focus on the critical shortage of nurses puts nurses at risk for representation as a health workforce commodity, rather than being recognized as an autonomous, knowledge-based profession without which the health of Canada's population is in jeopardy. Nurses' knowledge and professional role includes evaluation of their career, working conditions, and impact on patients and populations of care. The concern that nurses are leaving the profession can be analyzed within a feminist perspective related to autonomy and advocacy. The focus of this reflective commentary is to highlight, at a personal and collective level, that nurses are witnesses to the conditions fueling nursing shortages, the impact on the practice environment and the structural factors influencing these areas. We are therefore compelled to articulate the seriousness of our concerns and assert our knowledge and value as a profession.